Analisis Pengaruh Cleanliness, Ketebalan, dan Jenis Cat pada Material Baja A572 terhadap Daya Rekat Cat dan Biaya Proses Menggunakan Metode Taguchi-Grey Relational Analysis - Anggie Madhu Firdiandani; Farizi Rachman; Bayu Wiro Karuniawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
A general constructor company engaged in manufacturing and construction services produces steel structure components that go through several stages of the fabrication process, one of which is the finishing stage. At the finishing stage, the product is coated by painting to protect the product from corrosion. The adhesion of the paint to the substrate must meet the criteria to get a good quality of protection for the product. Products with poor quality or defects require a repair stage so that the product can be sent to consumers. However, the repair stage can cause the process costs at the finishing stage to be higher. To get a product of good quality so that the resulting product has high adhesion and low processing costs, research is needed to obtain the optimal combination of process parameters in the painting process. The process parameters studied were cleanliness, thickness, and type of paint. The experimental design used the Taguchi method in the form of an orthogonal L9(34) matrix with three replications and used Grey Relational Analysis. From the experimental results, it was found that the optimal combination of process parameters for adhesion strength and process costs simultaneously was cleanliness at level 2 with a value of Sa2 1/2, thickness at level 1 with a value of 100?m, and paint types at level 1 with surface tolerant epoxy. The cleanliness parameter gives a contribution percentage of 67.5482%, thickness is 16.4417% and the type of paint is 13.5329%.